Exploring university students’ readiness for the industrial revolution 4.0: a conceptualised framework - Poh, Joe Yee (2024)
The worldwide trend of embracing the Fourth Industrial Revolution is accelerating, however Malaysia has yet to extensively apply it. The purpose of this study is to look at the factors that influence Malaysian graduates' readiness for the Fourth Industrial Revolution. This research uses the Fourth Industrial Revolution and three independent variables: Technical Skills (TS), Problem-solving Skills (PS), and Interpersonal Skills (IS). This study collected pertinent data by a questionnaire. The questionnaire consisted of 25 questions, and 400 sets of replies were gathered. SPSS software was used to analyse the results. Of the three independent variables, TS, PS, and IS were shown to have a substantial effect on the graduate's preparation for the Fourth Industrial Revolution. This study covers research summary, literature review, methodology, data analysis, discussion, conclusion, and implications. The study's limitation is that it only examined cross sectional data to determine the skills and competences required in the labour market for implementing the Fourth Industrial Revolution. Furthermore, the data does not cover all additional skills and competencies required in developing countries